Corak dan Penafsiran Ayat Mawaris dalam Kitab Tafsir Marah Labid Karya Syekh Nawawi Al-Bantani - Zeti Isra Tri Oktafia .Z (Program Pascasarjana UIN Sultan Maulana Hasanuddin Banten, Jalan Jenderal Sudirman No. 30, Serang - Banten 42118, 2023)
This article discusses the verses of the Qur'an, which is one of the efforts to understand the existing studies. Discussing the right of inheritance where this right of inheritance becomes inheritance property for heirs, the division of inheritance is the division of inheritance when someone has died, who gets the right of inheritance is that there are criteria for each reason what has been explained in the Quran and legal requirements in Islam, the division of property that gets is certain people such as parents, The side of the father, the side of the mother and many more criteria that get and become heirs. and whoever gets the inheritance, this is already explained in the Qur'an in surah An-nisa in verses 11-12 and in verse 176 which is interpreted in the book of tafsir Marah Labid. Written by Sheikh Nawawi Al-Banthani. And the interpretation of the book of Marah Labid uses the method of interpretation of tahlili and ijmali and is patterned interpretation.